Progress in research on and classification of surgical methods of arthroscopic reconstruction of the ACL and ALL using a shared tendon graft through the femoral tunnel - Guo, Ziteng; Liu, Fei (Frontiers in Surgery, 2023)
Anterior cruciate ligament (ACL) tear is a common clinical injury, and ACL reconstruction has reached a very mature level. However, with the accumulation of cases, scholars found that isolated ACL reconstruction could not completely solve the problem of knee rotational stability. With the increase of understanding of knee joint structure, ACL combined with anterolateral ligament (ALL) reconstruction has been accepted by most scholars, and this operation has also achieved good clinical results.At present, there is no unified surgical method for ACL combined with ALL reconstruction. There are differences in bone tunnel location, reconstruction methods and graft selection. Compared with the independent reconstruction of ACL and ALL during the operation, the shared tendon graft reconstruction of ACL and ALL has the advantages of saving tendon and avoiding tunnel convergence. So far, there is no relevant literature to summarize the reconstruction of ACL and ALL with a shared tendon graft. This paper reviews the anatomic study of the ALL, the study of isometric points, and the surgical indications, surgical methods and classification of the shared tendon graft reconstruction of the ACL and ALL.